Bis(2-amino-3-methylpyridine-κN1)dichloridomercury(II) - Azadeh Tadjarodi; Keyvan Bijanzad; Behrouz Notash (Acta Crystallographica Section E, 2012)
In the title compound, [HgCl2(C6H8N2)2], the two independent HgII cations are each located on a twofold rotation axis and coordinated by two pyridine N atoms from two 2-amino-3-methylpyridine ligands and two Cl− anions in a distorted tetrahedral geometry. An intramolecular N—H...Cl hydrogen bond occurs in each independent complex molecule. Intermolecular N—H...Cl hydrogen bonds occur in the crystal structure.